Perfectionism as predictor of anxiety and depression - Lauri Korajlija, Anita; Jokić-Begić, Nataša; Begić, Dražen (2007)
A dual process model of perfectionism suggests that perfectionism has both positive and negative aspects. Positive perfectionism refers to cognitions and behaviors directed toward the achievement of certain high-level goals in order to achieve positive consequences, while negative perfectionism on other hand, refers to cognitions and behaviors directed towards the achievement of certain high-level goals in order to avoid or escape from negative consequences. Perfectionism is often linked to general anxiety and has been studied in relation to anxiety disorders (most often obsessive-compulsive disorder and social phobia). Research consistently confirms the relation between perfectionism and depression. The aim of this study was determine the way in which perfectionism (negative and positive) is linked to anxiety and depression. Participants included in study (N=124) where divided in three groups: group of clinically depressed participants, group of clinically anxious participants and control group. We used the following instruments: Beck depression Inventory, Stait-Trait anxiety Inventory and Positive and negative perfectionism scale. Results show that negative perfectionism is directly related to anxiety, and indirectly to depression (through anxiety as a mediator variable). Negative perfectionism by itself is a good predictor of anxiety and can be used as a good predictor of depression only in combination with trait anxiety. Due to the finding that positive perfectionism is not related either to depression nor anxiety, we can think of it as a desirable trait.
Projekt MZOS
ENG